Analisis Putusan Sela Perkara Mediasi Berhasil Harta Bersama (Studi Kasus Perkara No. 1471/Pdt.G/2019/PA.Sdn) - Ardliansyah, Moelki Fahmi; Istinganatul Khumaida; M. Arif Rahman Hakim; Fadhilah Nasrudin; Intan (Syakhsiyah Jurnal Hukum Keluarga Islam, 2024)
Interlocutory decisions are sacred in cases. Interlocutory decisions have various characteristics if they are to be issued, and the judge in resolving the case depends on the type and need for the case to use an interim decision or not. In joint property cases, of course, it is mandatory to carry out a local inspection and before carrying out a local inspection, the judge is obliged to issue an interim decision to carry out the local inspection. However, in the case of the Sukadana Religious Court which registered a unique case number, why is it unique because before the interim decision was issued there had been peaceful and successful efforts. And it is interesting to examine why when mediation is successful the case is continued and an interim decision is issued and the local examination continues. The research method uses normative juridical methods with a qualitative approach. The results of the deliberative research carried out, even if the mediation is successful to confirm whether joint assets exist or not, must still carry out a local inspection and the decision between the local inspections will still be read out.